Summation of Motor Unit Force in Passive and Active Muscle - Sandercock, T. G. (Exercise and Sport Sciences Reviews, 2005)
Nonlinear summation of force has been observed between motor units. The complex structure of muscle suggests many reasons why this could happen. When large portions of the muscle are active, however, the nonlinearities are small, and generally explained by stretch of the common elasticity. This suggests that the type of nonlinearity observed between motor units may not be physiologically significant.